The lady of the basement flat - Vaizey, George de Horne, Mrs., 1857-1917; Bellows, Elizabeth, 1842-1932 (Salt Lake City, UT : Project Gutenberg, 2007)
"The Lady of the Basement Flat" by Mrs. George de Horne Vaizey is a novel written in the late 19th century. The story revolves around two sisters, Evelyn and Kathleen Wastneys, with Evelyn feeling lost after Kathleen's marriage. To find purpose, Evelyn decides to adopt the persona of an elderly woman named Miss Harding and engage in acts of kindness in a lower-class London neighborhood, while their family life intersperses her adventures and leads to deeper connections. At the start of the story, we witness the aftermath of Kathleen's marriage and the toll it takes on Evelyn, who is left to grapple with her new reality. Evelyn's decision to rent a basement flat under the guise of an old woman represents her quest for identity and belonging. As Evelyn navigates her new life, she uncovers her compassion and desire to help others in her neighborhood, dealing with circumstances such as a sick neighbor's child. The initial chapters set the stage for her journey of self-discovery and the interplay between social class, personal sacrifice, and the quest for love in a changing world. (This is an automatically generated summary.)
Release date is 2007-10-20
Produced by Nick Hodson of London, England
Keywords: Single women -- Fiction; Irish -- England -- Fiction